2008
DOI: 10.1007/s00251-008-0284-4
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin haplotypes influence Brucella abortus infection in the water buffalo (Bubalus bubalis)

Abstract: A case-control study established that the haplotype pair HYA/HYA at the MBL (mannose binding lectin) locus of water buffalo is associated with resistance to Brucella abortus infection (P < 10(-7)) and the haplotype pairs LYD/LYD with susceptibility to the same pathogen (P < 10(-7)). The subjects included in the present study were tested twice-at a 1-month interval-for the presence of anti-B. abortus antibodies in the serum by agglutination, complement fixation and flow cytometry. Cases (335 subjects) included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…SNPs of MBL1 gene in various breeds of pigs were found to be associated with impaired disease resistance [25]. Both MBL1and MBL2 gene mutations were found to be having impact on susceptibility to different infections [26]. Variations in the coding and the non-coding regions of the MBL gene in various species resulted in innate immune dysfunction [23].…”
Section: Discussionmentioning
confidence: 99%
“…SNPs of MBL1 gene in various breeds of pigs were found to be associated with impaired disease resistance [25]. Both MBL1and MBL2 gene mutations were found to be having impact on susceptibility to different infections [26]. Variations in the coding and the non-coding regions of the MBL gene in various species resulted in innate immune dysfunction [23].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with SNPs, haplotypes are likely to exert a greater effect on traits (Capparelli et al, 2008). In addition, haplotype analysis is more comprehensive than single-locus analysis (Fallin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Variations of both MBL1 and MBL2 have been associated with resistance to infections such as S. aureus in mice (Shi et al, 2004), K88+ E. coli, Streptococcus suis, Actinobacillus pleuropneumoniae, Mycoplasma spp, and circovirus 2 in pigs (Lillie et al, 2007), B. abortus in water buffalo (Capparelli et al, 2008), Neorickettsia risticii and Clostridium spp in horses (Podolsky et al, 2006), and meningococcal and E. coli infections in humans (Neth et al, 2000;Eisen and Minchinton, 2003;Smithson et al, 2007). Because bacteria are the most common causes of mastitis in cows, analysis of bovine MBL2 SNPs may contribute to the discovery of their association with mastitis resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired disease resistance has been associated with 3 single-nucleotide polymorphisms (SNPs) within the coding region of MBL1 in various breeds of pigs (Lillie et al, 2006). Studies of human MBL-C have revealed that 3 SNPs in the collagen-like domain and 3 additional mutations within the MBL2 promoter region can affect the assembly or formation of MBL-C, thus contributing to a low level of plasma MBL and innate immune dysfunction (Madsen et al, 1994(Madsen et al, , 1998Capparelli et al, 2008). Accumulating data have revealed that haplotype combinations of human MBL2 SNPs generate increasing susceptibility to various bacterial, viral, and parasitic diseases as well as to systemic lupus erythematosus, rheumatoid arthritis, hepatitis, cystic fibrosis, and ischemiareperfusion injury (Eisen and Minchinton, 2003;Holmskov et al, 2003;Takahashi et al, Genetics and Molecular Research 11 (4): 3744-3754 (2012) Z.L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation